Manual de funciones para la exportadora AGROCHONG-QUI cía. Ltda., año 2016. - Oña Mera, Stalin Fernando (2016)
The research project was made to develop a manual of functions for Exportadora AGROCHONG-QUI Cia. Ltda., To improve work performance and operational development of human talent, to effect the activities in each work area in export were identified, the characteristics of each office functions, levels of responsibility, the possibility of simplification were established and eliminating unnecessary operations. To proceed with development of the research was used to the types of field research, by implementing surveys, the same as were applied to the staff of the company, in the same way the interview technique was employed to General Manager and Head Human Talent, in order to answer the questions and specific objectives of this research work. According to the results of the field study, it was determined that the Exportadora AGROCHONG-QUI Cia. Ltda., No manual functions, which affects organizational and operational performance, preventing administrative staff and field meet the development of activities within their respective areas. The implementation manual functions Exportadora AGROCHONG-QUI Cia. Ltda., Will be an important tool that define administrative positions, thanks to the requirements for the operational and functional staff to perform responsibly, efficiently and effectively the development of the activities of the company.